THORACIC EPIDURAL VERSUS GENERAL ANAESTHESIA FOR LAPAROSCOPIC CHOLECYSTECTOMY: A RANDOMIZED CONTROLLED TRIAL - Ahmad, Fariha; Liaquat Ali; Madiha Ahmed; Mohammed Yasrab; Arshad Khusdil; Samiullah (Journal of Ayub Medical College Abbottabad, 2022)
Background: Laparoscopic cholecystectomy is one of the most commonly performed surgeries worldwide. Aim of our study was to compare the effectiveness of thoracic epidural anaesthesia with general anaesthesia for Laparoscopic cholecystectomy in terms of changes in blood pressure during surgery, postoperative pain, respiratory complications and average length of hospital stay. It was a randomized controlled trial conducted from 1stOctober 2018 to 31st October 2019. Methods: Eighty-two patients planned to undergo elective laparoscopic cholecystectomy were randomly divided into two groups, T and G. In Group T all patients underwent laparoscopic cholecystectomy under thoracic epidural anaesthesia with 12 ml of 0.25% bupivacaine and 1% lignocaine plain whereas in group G all patients underwent surgery under general anaesthesia. Intra-operative mean arterial pressure (MAP) and postoperative opioid consumption in first 24hrs were recorded as primary outcomes whereas presence or absence of respiratory complication and duration of hospital stay as secondary outcome. Results: Out of 82 patients, 41 patients underwent laparoscopic cholecystectomy under thoracic epidural anaesthesia and 41 patients had surgery under general anaesthesia. Mean arterial pressure was lower in Group T and the difference was statistically significant. The average time of first complaint of postoperative pain in Group T was 5.4±1.26 hours as compared to less than 0.79±0.25 hours in Group G. Patients in group T required lower doses of opioid analgesia in first twenty-four hours as compared to patients in group G. Mean hospital stay in group T was 1 day as compared to 3 days in group G. Conclusion: Thoracic epidural anaesthesia provides a better alternative to general anaesthesia for Laparoscopic cholecystectomy with lower intraoperative mean arterial blood pressure, 24 hours postoperative consumption of opioids, respiratory complications and length of hospital stay.